THE GOVERNMENT AND BUSINESS COLLABORATION IN DESIGNING INDUSTRIAL POLICY IN THE RUSSIAN RAILWAY MACHINE-BUILDING - Diana Pereversieva; Viacheslav А. Lipatov (Статистика и экономика)
The article is devoted to improvement of the mechanism of the government and business collaboration in designing industrial policy. Materials and data of the passenger railway machine-building industry were basis for the analysis. The article draws a lot of attention to regional aspects of the issue. Proposals for the improvement of political mechanisms of the coordination of interests were worked out based on the business proposals and positions of government bodies.